Physisorption controls the conformation and density of states of an adsorbed porphyrin - Jarvis, Samuel Paul; Taylor, S.; Baran, J.D.; Thompson, D.; Saywell, Alexander; Mangham, Barry; Champness, Neil R.; Larsson, J.A.; Moriarty, Philip (American Chemical Society, 2015)
Conformational changes caused by adsorption can dramatically affect a molecule’s properties. Despite extensive study, however, the exact mechanisms underpinning conformational switching are often unclear. Here we show that the conformation of a prototypical flexible molecule, the freebase tetra(4-bromophenyl) porphyrin, adsorbed on Cu(111), depends critically on its precise adsorption site and that, remarkably, large conformational changes are dominated by van der Waals interactions between the molecule and the substrate surface. A combination of scanning probe microscopy, single-molecule manipulation, DFT with dispersion density functional theory, and molecular dynamics simulations show that van der Waals forces drive significant distortions of the molecular architecture so that the porphyrin can adopt one of two low-energy conformations. We find that adsorption driven by van der Waals forces alone is capable of causing large shifts in the molecular density of states, despite the apparent absence of chemical interactions. These findings highlight the essential role that van der Waals forces play in determining key molecular properties.